PayKit ЯК ІНСТРУМЕНТ ЦИФРОВОЇ ТРАНСФОРМАЦІЇ В УПРАВЛІННІ БІЗНЕСОМ У СФЕРІ HoReCa - Fostolovych, Valentyna (Zhytomyr Ivan Franko State University, 2025)
Globalization and intensive penetration of digital technologies into all spheres of economic activity and business require a quick response to ensure a comfortable environment for a potential client. Hospitality enterprises need a special approach to the integration of digital technologies and the expansion of the range of services in the cloud and digital environment. Digitalization has become a challenge and a tool for continuous improvement for HoReCa enterprises.  Ensuring business competitiveness becomes possible through the constant integration of innovative technologies and the development of strategies that will contribute to the growth of economic, social and environmental efficiency. The article examines the expediency and identifies the need to implement the PayKit POS system in the activities of hotel and restaurant business establishments. The introduction of digital tools into the enterprise management system and the technology of implementing business processes change the functionality of the enterprise and make it convenient for the guest to receive services. In the process of the study, it was noted that the PayKit POS system helps to optimize business processes from the provision of services to the tools of institution management technology. The low cost of using cloud services with advanced functionality contributes to increasing profitability and ensures the implementation of a competitive business. An effective CRM system, automation of finances, warehouse operations and an analytics module provide a personalized approach to the provision of services and provide an opportunity to study needs and satisfy them for each guest individually.  Such a software solution for the automation of both production processes and the business management system as a whole provides quick service of all cash operations (cash and through the contactless payment system), accounting of production stocks in the warehouse (from receipt to disposal by sale or write-off, the possibility of residue control). The advanced functionality of the PayKit POS system provides the ability to develop loyalty programs, ensuring effective management of sales in remote mode from any gadget. The capabilities of this software solution, when integrated into the business process, ensure the operation of the mobile cash register, accounting and control functions at the enterprise, provide the opportunity to carry out fiscalization thanks to the built-in software registrar of settlement operations. The advanced capabilities of the analytics module ensure the formation of sales reports, financial indicators and analysis of business indicators, which makes business management easy and efficient. Network management is affordable and convenient due to the creation of a single cloud cabinet. Therefore, the integration of the PayKit POS system into HoReCa enterprises simplifies the organization of business processes and provides ample opportunities for the formation of a competitive business.